Office Coordination Between Intelligence and Criminal Investigation in Determining Suspects of Theft in the Legal Area of Badung Resort Police - Bayu Arya Pratama, I Gede; Sihotang, Erikson; Nurmawan Damanik, Siti (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Police intelligence is critical in supporting criminal investigations, particularly identifying suspects in theft cases. In the jurisdiction of the Badung Resort Police, police intelligence acts as the eyes and ears responsible for conducting early detection and providing critical information to assist criminal investigations and prosecutions. However, there are still challenges in coordination and communication between intelligence and criminal investigation units, affecting the effectiveness of law enforcement efforts. This study aims to evaluate the role of police intelligence in supporting the criminal investigation unit in identifying theft suspects in Badung Resort Police. The results showed that effective coordination between Intelligence and criminal Investigation plays an important role in determining suspects, despite internal constraints such as limited human resource skills and external constraints such as lack of community cooperation. The implication of this research is the need to improve the quality of human resources in the Police and strengthen cooperation with the community to increase the effectiveness of law enforcement.